New pathways for progress in multilateral trade negotiations in agriculture - Cahill, Carmel; Tangermann, Stefan; Brink, Lars; Fan, Shenggen; Glauber, Joseph W.; Gonzalez, Anàbel (2021)
The creation of the WTO in 1994 marked a new departure in multilateral trade relations, for several reasons, among them the successful inclusion of a specific agreement on agriculture, putting an end to the de facto exclusion of the sector from multilateral disciplines which had persisted since the founding of the GATT in 1948. By accepting the Uruguay Round Agreement on Agriculture, Members of the fledgling WTO acknowledged the disarray which had been created by unbridled subsidies and trade restrictions in the sector and set about rectifying this situation. Moreover, in agreeing Article 20 on the continuation of the reform process, Members also implicitly acknowledged that the Agreement on Agriculture (henceforth AoA) was merely a beginning. Explicitly it was agreed that negotiations for continuing the reform process would begin one year before completion of implementation, that is in the year 2000. These negotiations were then made an element of the new round of multilateral trade negotiations launched in 2001 and known as the Doha Development Agenda (DDA).